TARI GENDING SRIWIJAYA: MORALITAS DALAM REFLEKSI HISTORIS CIVIL SOCIETY - Yoan Mareta; Sariyatun Sariyatun; Leo Agung Sutimin (Patanjala: Journal of Historical and Cultural Research, 2019)
Tari Gending Sriwijaya adalah tari tradisional yang mengandung unsur budaya Palembang di setiap bagiannya. Setelah memicu kontroversi kontemporer yang menganjurkan penghapusan tari Gending Sriwijaya, tulisan ini hadir sebagai ungkapan kritis menolak konsepsi tersebut. Pentingnya warisan budaya dalam konteks kebudayaan haruslah disajikan sebagai acuan edukasi sebab kehadirannya merupakan bentuk historical value. Tujuan penulisan ini adalah kajian tari Gending Sriwijaya berfokus pada tafsir gerak yang diperagakan oleh penari melalui metode penelitian fenomenologi, guna mencari nilai moralitas yang terkandung dalam gerak tari dan mencari refleksi historis civil society dalam orientasi nilai. Hasil pembahasan: 1) Historisitas tari Gending Sriwijaya; 2) Tafsir gerak tari Gending Sriwijaya dalam kajian nilai moralitas; 3) Nilai refleksi historis civil society. Tari Gending Sriwijaya sebaiknya menjadi orientasi logis dalam pengejawantahan tari sebagai refleksi nilai historis, sebab kebutuhannya menyokong adab generasi mendatang yang berkontribusi terhadap kesuksesan visi civil society.Gending Sriwijaya dance is a traditional dance that contains elements of Palembang culture in every part of it. After triggering a contemporary controversy that advocated the abolition of the Gending Sriwijaya dance, this paper came as a critical expression of rejecting the claim. The importance of cultural heritage must be presented as an educational reference because its presence is a form of historical value. The purpose of this writing is the study of Gending Sriwijaya dance which focuses on interpretations of motion that are exhibited by dancers through phenomenology research methods, in order to find the moral values contained in dance movements and seek historical reflection of civil society. Results of discussion: 1) The historicity of the Gending Sriwijaya dance; 2) The moral values contained in the motions of the Gending Sriwijaya dance; 3) Historical reflection values of civil society. Gending Sriwijaya dance should be a logical orientation in the embodiment of dance as a reflection of historical value because its usefulness as a support for future generations of who will contribute to the success of vision of civil society.